2009
DOI: 10.7326/0003-4819-151-10-200911170-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short Course of Eszopiclone on Continuous Positive Airway Pressure Adherence

Abstract: Compared with placebo, a short course of eszopiclone during the first 2 weeks of CPAP improved adherence and led to fewer patients discontinuing therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
56
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 33 publications
0
56
0
4
Order By: Relevance
“…This may reflect improvements in sleep initiation and reductions in insomnia, which has been shown to enhance therapeutic adherence with CPAP among non-PTSD patients. 29 While CPAP was used more often and for longer periods among PTSD patients using sedating medications, adherence was still lower than that observed in the control group, suggesting that the diminished use of CPAP among patients with PTSD is likely multifactorial.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This may reflect improvements in sleep initiation and reductions in insomnia, which has been shown to enhance therapeutic adherence with CPAP among non-PTSD patients. 29 While CPAP was used more often and for longer periods among PTSD patients using sedating medications, adherence was still lower than that observed in the control group, suggesting that the diminished use of CPAP among patients with PTSD is likely multifactorial.…”
Section: Discussionmentioning
confidence: 91%
“…The majority of our patients were habitually using sedating medications; prior studies have shown that non-benzodiazepine sedative-hypnotics may improve CPAP adherence. 29,50,51 This likely diminished the observed differences in CPAP use, as we found that patients using sedating agents had increased use of CPAP than patients not using sedatives. Despite this, PTSD still impaired CPAP adherence regardless of concomitant sedative use.…”
mentioning
confidence: 80%
“…21 A prospective use of short-term eszopiclone use improved CPAP use from 2.4 to 3.6 hours. 13 Other interventions that improved CPAP compliance were in cases where baseline or placebo group use was under 5 hours ( Table 6). Our placebo group's average compliance was already 6.5 h/night.…”
Section: Discussionmentioning
confidence: 99%
“…12 In contrast, Lettieri et al found that eszopiclone for the fi rst 14 nights of CPAP was associated with greater long-term compliance than placebo. 13 Their group, in a retrospective study, also found an association between hypnotic (mostly zolpidem, and to lesser extent eszopiclone) use during CPAP titration and improved compliance at 4-6 weeks.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 91%
“…23 Other intervention-based trials aimed at improving CPAP adherence have employed sample sizes ranging from 100 to 373 participants. [23][24][25][26][27] However, the current pilot study aimed to recruit much less than that to assess feasibility and obtain preliminary data.…”
Section: Sample Size Estimationmentioning
confidence: 99%